Peran Rasa Syukur terhadap Kebahagiaan Remaja Korban Perceraian - Nurhazizah, Arifa (Jurnal Riset Agama, 2022)
Having a whole family and harmony is the peace of every individual, where a child can feel the role of both parents in a family. But not very few families fail to harmonize, which is the result of an unexpected breakup. The direct consequences of divorce are emotional distress and behavioural problems, as well as the results of research on many divorces that reveal that high-risk children are experiencing psychological, social and academic development problems compared to non-divorced parents’ families. In teenagers, it’s a time when a person’s social consciousness is going to get higher and when social pressure comes out every day, various problems can occur in teenagers, because teenagers’ behavior is still not able to adapt to various demands from the environment. Until the role of the elderly is fully attained, neither happiness is fully attained by the family. The purpose of this research is to know the role of gratitude for the happiness of student SMA-IT Jaisyul Quran Nagreg who are divorced parents. The method used is a qualitative method that focuses on descriptive data. To get a proper description, writers process data by analyzing field data. where data sources come from observations and interviews and other literature related to the research theme. The results of this study show that gratitude plays an important role in bringing happiness to the adolescent victims of divorce, and that can have an impact on the lives of both social and academic students.